Breakage modeling of needle-shaped particles using the discrete element method. (August 2019) - Kumar, R.; Ketterhagen, W.; Sarkar, A.; Curtis, J.; Wassgren, C.
Graphical abstract: Highlights: Breakage of sphero-cylindrical particles in an attrition cell is modeled using DEM. Smaller particles accumulate upstream of attrition cell base and blade face. Rate of breakage events decreases rapidly as particle size decreases. PSD becomes independent of initial PSD after sufficient work on the particles. PBM breakage rate and daughter distribution correlations determined from DEM data. Abstract: This paper models the breakage of large aspect ratio particles in an attrition cell using discrete element method (DEM) and population balance (PB) models. The particles are modeled in DEM as sphero-cylinders. The stresses within each particle are calculated along the particle length using beam theory and the particle breaks into two parts if the stress exceeds a critical value. Thus, the size distribution changes with time within the DEM model. The DEM model is validated against previously published experimental data. The simulations demonstrate that particle breakage occurs primarily in front of the attrition cell blades, with the breakage rate decreasing as the particle sizes decrease. Increasing the particle elastic modulus, decreasing the particle yield strength, and increasing the attrition cell lid stress also increase the rate of breakage. Particles break most frequently at their center and the daughter size distribution normalized by the initial particle size is fit well with a Gaussian distribution. Parametric studies in which the initial particle size distribution varies demonstrate that the particle sizes approach a distribution that is independent of the initial state after a sufficient amount of work is done on the particle bed. A correlation for the specific breakage rate is developed from the DEM simulations and used within a PB model along with the daughter size distribution fit. The PB model also clearly shows that the particle size distribution becomes independent of the initial size distribution and after a sufficiently long time, is fit well with a log-normal distribution.